Evaluation of the mtDNA-COII Region Based Species Specific Assay for Identifying Members of the Anopheles culicifacies Species Complex. - Arulsamy Mary Manonmani; Ashok Kumar Mathivanan; Candassamy Sadanandane; Purushothaman Jambulingam (Tehran University of Medical Sciences, 2013)
Background: Anopheles culicifacies, a major malarial vector has been recognized as a complex of five sibling species, A, B, C, D and E. These sibling species exhibit varied vectorial capacity, host specificity and susceptibility to malarial parasites/ insecticides. In this study, a PCR assay developed earlier for distinguishing the five individual species was validated on samples of An. culicifacies collected from various parts of India. Methods: The samples were initially screened using the rDNA-ITS2 region based primers which categorised the samples into either A/D group or B/C/E group. A proportion of samples belonging to each group were subjected to the mtDNA-COII PCR assay for identifying individual species. Results: Among the 615 samples analysed by rDNA-ITS2 PCR assay, 303 were found to belong to A/D group and 299 to B/C/E group while 13 turned negative. Among 163 samples belonging to A/D group, only one sample dis- played the profile characteristic of species A and among the 176 samples falling in the B/C/E group, 51 were identi- fied as species B, 14 as species C and 41 as species E respectively by the mtDNA-COII PCR assay. Samples exhib- iting products diagnostic of B/C/E, when subjected to PCR-RFLP assay identified 15 samples as species E. Conclusion: Validation of the mtDNA-COII PCR assay on large number of samples showed that this technique can- not be used universally to distinguish the 5 members of this species complex, as it has been designed based on mi- nor/single base differences observed in the COII region.